2017
DOI: 10.1073/pnas.1707993114
|View full text |Cite
|
Sign up to set email alerts
|

pH-sensitive vibrational probe reveals a cytoplasmic protonated cluster in bacteriorhodopsin

Abstract: Infrared spectroscopy has been used in the past to probe the dynamics of internal proton transfer reactions taking place during the functional mechanism of proteins but has remained mostly silent to protonation changes in the aqueous medium. Here, by selectively monitoring vibrational changes of buffer molecules with a temporal resolution of 6 µs, we have traced proton release and uptake events in the light-driven proton-pump bacteriorhodopsin and correlate these to other molecular processes within the protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
70
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(72 citation statements)
references
References 100 publications
(175 reference statements)
2
70
0
Order By: Relevance
“…(27). More recently, it was revealed that proton uptake in bR utilizes a cluster of residues to stabilize interactions of the proton donor with bulk cytoplasmic waters, leading to modulation of the later stages in the photocycle (28). PR does not possess a corresponding aspartic acid residue, so it would make sense that the proton donor behaves differently from bR.…”
Section: Deprotonation Of E108 Leads To An Increase In Hydration Frommentioning
confidence: 99%
See 1 more Smart Citation
“…(27). More recently, it was revealed that proton uptake in bR utilizes a cluster of residues to stabilize interactions of the proton donor with bulk cytoplasmic waters, leading to modulation of the later stages in the photocycle (28). PR does not possess a corresponding aspartic acid residue, so it would make sense that the proton donor behaves differently from bR.…”
Section: Deprotonation Of E108 Leads To An Increase In Hydration Frommentioning
confidence: 99%
“…This rapid release of the helical bundle in bR (i.e., ''latch mechanism'') has a twofold purpose: 1) to form the water wire and 2) to prevent backflow of protons that impede the photocycle (27). Although PR has a glutamic acid (E108) in the same position as the proton donor in bR, it lacks a pair of glutamic acids that act as a proton uptake complex (28) as well as a hydrogen-bonding partner in helix B that lies directly across from the proton donor (12). In addition, an acidic residue as the proton donor is not conserved among other PR-like proton pumps, such as a lysine in Elasmotherium sibiricum rhodopsin (29) and a histidine on helix B in eubacterial proton pumps (30).…”
Section: Introductionmentioning
confidence: 99%
“…Bacteriorhodopsin in AuAgNR SPCs showed the highest proton transporting rate, which was about 1.9‐ and 2.7‐fold higher than those of AuNP and SiO 2 NP SPCs, respectively. Given the negligible difference in cargo release kinetics of the three CCs studied above (Figures S11–13) and the well‐known accelerated migration of protons assisted by mobile buffer molecules, the possibility that the proton diffusion was the rate‐limiting factor could be excluded. The ability of plasmonic nanostructures to strongly localize incident light close to their surface has been shown to greatly enhance the optical properties of proximal (bio‐)molecules, which generally requires strong spectral overlap between the plasmonic resonance and (bio‐)molecule absorption/emission band .…”
Section: Methodsmentioning
confidence: 99%
“…Since its discovery in 1971 [ 1 ], the light-driven proton pump bacteriorhodopsin (BR) from the extreme halophilic archaeon Halobacterium salinarum (previously known as Halobacterium halobium ) has become an intensively studied model membrane protein for proton translocation across biological membranes [ 2 , 3 , 4 , 5 ], photochemical events in proteins [ 6 , 7 , 8 , 9 ], photophosphorylation [ 10 , 11 , 12 ] and structural studies [ 13 , 14 , 15 , 16 ]. The use of BR to study proton transport across membranes in different time scales using time-resolved serial femtosecond crystallography at X-ray free electron lasers [ 17 , 18 , 19 , 20 ] and as an alignment tool for NMR studies [ 21 ] highlights its significant contribution to emerging technologies.…”
Section: Introductionmentioning
confidence: 99%